Influence of Bridgman process conditions on microstructure and porosity of single crystal Ni-base superalloy CMSX-4. (December 2014) - Matuszewski, K.; Matysiak, H.; Jaroszewicz, J.; De Nolf, W.; Kubiak, K.; Kurzydłowski, K. J.
<x content-type="archive" xml:space="preserve">Abstract</x> Synchrotron radiation micro-X-ray fluorescence and micro-X-ray diffraction analysis, micro-computed tomography and transmission electron microscopy were used to investigate the microstructure of turbine blades made of a second generation nickel based superalloy CMSX-4 manufactured by investment casting process via Bridgman technique. The dependence of microstructure on process parameters, among others, on the withdrawal rate was analysed. The results set the stage for optimising the microstructure of the blades in terms of their mechanical properties.